Plan estratégico para la unidad de internacionalización de una escuela de postgrado - Borda Reyes, Armando Juan (2023)
The following report outlines the strategic planning process for the internationalization unit of a prominent business school in Peru. To accomplish this, I established the objectives for the unit, conducted a comprehensive strategic diagnosis, and executed a thorough internal analysis. Building on this groundwork, I formulated various alternative strategies for the internationalization unit. This process entailed defining the unit's general strategy, as well as crafting SWOT and SPACE matrices. These analytical tools revealed that the internationalization unit maintains a conservative strategic profile. Next, I utilized the Quantitative Strategic Planning Matrix to prioritize a range of feasible courses of action at the unit level. Consequently, it is recommended that the unit continues to center its efforts on leveraging its privileged access to relevant international networks to deliver distinctive, esteemed, and memorable experiences to the students of the business school. Finally, I developed a strategic map that delineates the key indicators and goals to be attained for each strategic objective.